Cuma Günündeki İcabet Vakti ile İlgili Rivayetlerin Değerlendirilmesi - Bingül, Mahmut (Scientific Journal of Faculty of Theology, 2020)
In this study, which is named “Examining Hadiths About Times That Prayers Are Accepted On Friday”, the hadiths about the time that the prophet Muhammad’s pointed out that prayers will be accepted are examined. This study consists of introduction and two parts. In the first part, various hadiths related to the time when the prayers were accepted on Friday were analyzed in terms of sened. Different variants of hadiths have been determined and schemas of isnad have been created. Then, general information about narrators in the first hadith source that can be reached has given. To examine the narrators in all of the seneds one by one was found not suitable for the volume of this study and was found unnecessary. Because a general opinion has been formed with the narrators in the first source obtained. Among the hadiths, famous hadiths that point to the uncertainty of time and one for noon and afternoon has evaluated. The hadiths about the narrators given informations in the Cerḥ ve’t-taʿdîl books was later examined holistically. In this context, a general investigation was carried out on münteha, number of seneds, ittiṣal, and ṣıḥḥat. In the second part, some evaluations about these hadiths are stated. Although there are differences between the hadiths, the minimum common words and meanings were determined and text evaluation has made on them. Then, various opinions and hadiths were analyzed about when prayers were accepted. Among these, famous views were given together with their first available sources. The evidence on which the opinion-holders were based was examined. Then, some of the suggestions made about this time by some circles and the solution methods of the dispute between the hadiths were expressed.